Klasifikasi Risiko Hipertensi menggunakan Fuzzy K-Nearest Neighbor - Deby Chintya; Budi Darma Setiawan; Sutrisno Sutrisno (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Hypertension, also known as high blood pressure, is a condition where there's increase of blood pressure above the normal level of 120/80 mmHg. Hypertension can cause cardiovascular disease and increased death risk by coronary heart disease and stroke. According to Riset Kesehatan Dasar in Indonesia, hypertension is the most prevalent health problems with 25,8% percentage in 2013. Development of classification system for hypertension risk can be used to detect early hypertension disease. Classification of hypertension risk in this research uses Fuzzy K-Nearest Neighbor method, with Information Gain feature selection. Accuracy value resulted from the test is 84.0002% with value k=5 using 6 features of blood pressure, fitness, age, fatty foods consumption and caffeine consumption.